Efektivitas Media Augmented Reality Berbasis Smartphone Terhadap Kemampuan Komunikasi Visual dan Motivasi Siswa Pada Pembelajaran Biologi : (The Effectiveness of Smartphone Based Augmented Reality Media on Visual Communication Ability and Student Motivation in Biology Learning) - Muhammad Nurfaizi Supriyadi; Billyardi Ramdhan; Aa Juhanda (BIODIK, 2022)
Limited technology and information, as well as teachers who do not maximize the use of technology in learning, it is necessary to have learning media that utilize technology that can facilitate an educator in conveying material or information to educators. The technology that is currently being developed is Augmented Reality (AR) technology. The use of technology and information has also changed the way of communication. The era of the 21st century demands that every student be able to communicate visually, especially in biology materials whose concepts are partly abstract and require visual assistance. This study aims to determine the effectiveness of the use of Augmented Reality on the visual communication skills of students in one of the high schools in Sukabumi Regency. The method used in this research is Quasi-experiment (quasi-experiment). The research design used is Posttest-Only Control Group Design with purposive sampling. This research was conducted on class XI students in the 2021/2022 academic year. The instrument used is in the form of a Mind Map task. The research data shows that learning using Augmented Reality can train students' visual communication with the visible improvement of the results of making Mind Map, namely the average overall score of 77% in the good category, with the results on the Mind Map task 1 obtained an average of 72% and Mind Map task 2 obtained an average of 82% and the average of student motivation is 3,85 with good category. So it can be concluded that the use of Augmented Reality learning media has an effect on increasing students' visual communication skills and is useful in the learning process in measuring students' skills and student motivation. Key words: Augmented Reality, Visual communication, Student Motivation Â  ABSTRAK Penggunaan teknologi dan informasi juga merubah cara komunikasi. Era abad 21 ini menuntut agar setiap siswa mampu berkomunikasi visual, terutama dalam materi biologi yang konsepnya sebagian bersifat abstrak dan memerlukan bantuan visual. Penelitian ini bertujuan untuk mengetahui Efektivitas penggunaan media pembelajaran Augmented Realityterhadap kemampuan komunikasi visual siswa di salah satu SMA yang berada di Kabupaten Sukabumi. Metode yang digunakan pada penelitian ini adalah Quasi-experiment (eksperimen semu). Desain penelitian yang digunakan adalah Posttest-Only Control Group Design dengan teknik pengambilan sampel Purposive Sampling. Penelitian ini dilakukan pada siswa kelas XI tahun ajaran 2021/2022. Instrumen yang digunakan ini berupa tugas pembuatan Mind Map. Data hasil penelitian menunjukan pembelajaran menggunakan media pembelajaran Augmented Reality dapat melatih komunikasi visual siswa dengan terlihatnya peningkatan dari hasil pembuatan Mind Map yaitu rata rata nilai keseluruhan sebesar 77% dengan kategori baik, dengan hasil pada tugas Mind Map 1 diperoleh rata-rata sebesar 72% dan tugas Mind Map 2 diperoleh rata-rata sebesar 82% dan rata-rata nilai motivasi siswa sebesar 3,85 dengan kategori baik. Sehingga dapat disimpulkan bahwa penggunaan media pembelajaran Augmented Reality berpengaruh terhadap peningkatan kemampuan komunikasi visual siswa dan berguna dalam proses pembelajaran dalam mengukur kemampuan keterampilan siswa dan juga motivasi siswa .Â  Kata kunci: Augmented Reality, Komunikasi visual, Motivasi Siswa